Plasma Metabolic Profiling of Pediatric Sepsis in a Chinese Cohort - Li, Guo-Bang; Hu, Hong-Rong; Pan, Wen-Feng; Li, Bo; Ou, Zhi-Ying; Liang, Hui-Ying; Li, Cong (Frontiers in Cell and Developmental Biology, 2021)
Sepsis represents one of the most pressing problems in pediatrics, characterized by pathogenic bacteria invading the blood, growing and multiplying in the blood circulation, ultimately causing severe infections. Most children with sepsis have a rapid disease onset, and frequently exhibit sudden high fever or first chills. Here we performed comprehensive metabolomic profiling of plasma samples collected from pediatric sepsis patients, to identify specific metabolic alterations associated with these patients (n = 84, designated as case subjects) as compared to healthy cohorts (n = 59, designated as control subjects). Diagnostic models were constructed using MetaboAnalyst, R packages, together with multiple statistical methods such as orthogonal partial least squares-discriminant analysis, principal component analysis, volcano plotting, and One-way ANOVA. Our study revealed a panel of metabolites responsible for the discrimination between case and control subjects, with high predictive value of prognosis. Moreover, significantly altered metabolites in sepsis survivors versus deceased patients (nonsurvivors) were identified as those involved in amino acids, fatty acids, and carbohydrates metabolism. Nine metabolites including organic acids and fatty acids were also identified with significantly higher abundance in sepsis patients with related microbes, implicating greater potentials to distinguish bacterial species using metabolomic analysis than blood culture. Pathway enrichment analysis further revealed that fatty acid metabolism might play an important role in the pathogenesis of sepsis.